A future research agenda on export marketing and international marketing themes: a Delphi approach. (26th January 2023) - Coudounaris, Dafnis N.
Based on 11 export marketing experts of the editorial board of International Journal of Export Marketing ( IJEXPORTM ) and five international marketing experts from IJEXPORTM, this study investigates the possible evolution of export/international marketing in the next 15 years. In Round 1, the study uses two surveys which asked participants to complete questionnaires during January-March 2020. Additionally, in Round 2 during May-June 2022, the study uses the Delphi approach in asking an additional 12 experts in export/international marketing to evaluate the initial research themes. Furthermore, the author uses broad categories of research themes derived from the two lists of the initial research themes. The Round 1 study reveals through the tool of dendrogram 17 broad categories of research themes related to export marketing, and 13 broad categories of research themes related to international marketing. Particularly, digitalisation and social media are two new themes of both export and international marketing.